Progressive Multifocal Leukoencephalopathy in AIDS: Are There Any MR Findings Useful to Patient Management and Predictive of Patient Survival? - Judith Donovan Post, M.; Yiannoutsos, Constantin; Simpson, David; Booss, John; Clifford, David B.; Cohen, Bruce; McArthur, Justin C.; Hall, Colin D. (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: While MR findings in progressive multifocal leukoencephalopathy (PML) have been described previously, usually in retrospective studies with limited sample size, what has not been well addressed is whether any are predictive of longer survival. Our participation in a large prospective clinical trial of AIDS patients with biopsy-proved PML and MR correlation allowed us to test our hypothesis that certain MR features could be found favorable to patient survival.METHODS: The patient cohort derived from a randomized multicenter clinical trial of cytosine arabinoside for PML. Pretreatment T1- and T2-weighted noncontrast images (n = 48) and T1-weighted contrast-enhanced images (n = 45) of 48 HIV-positive patients with a PML tissue diagnosis as well as the follow-up images in 15 patients were reviewed to determine signal abnormalities, lesion location and size, and the presence or absence of mass effect, contrast enhancement, and atrophy, and to ascertain the frequency of these findings. A statistical analysis was performed to determine if any MR abnormalities, either at baseline or at follow-up, were predictive of patient survival.RESULTS: No MR abnormalities either on univariate or multivariate analysis significantly correlated with patient survival, with the exception of mass effect, which was significantly associated with shorter survival. The mass effect, however, always minimal, was infrequent (five of 48). More severe degrees of cortical atrophy and ventricular dilatation, lesion location and size, and other MR variables were not predictive of outcome.CONCLUSION: Except for mass effect, we found no MR findings predictive of the risk of death in patients with PML. The mass effect, however, was so infrequent and minimal that it was not a useful MR prognostic sign.